Pengaruh Pengenalan Merek dan Sikap terhadap Merek terhadap Minat Melanjutkan Kepesertaan BPJS Ketenagakerjaan: Bukti Empiris dari Peserta Program Dana Bagi Hasil Sawit di Kabupaten Ogan Komering Ilir - Muhammad Affandi; Sulastri; Welly Nailis (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines whether brand recognition and brand attitude influence participants' intention to continue BPJS Ketenagakerjaan membership after contribution assistance provided under the Palm Oil Revenue Sharing Fund program ends. Using a quantitative cross-sectional survey, data from 110 participants in Ogan Komering Ilir Regency were analyzed through multiple linear regression. Brand recognition and brand attitude had positive and significant effects on continuance intention, both simultaneously and individually; brand attitude was the strongest predictor. The findings imply that clearer program communication and consistently positive service experiences can strengthen participants' willingness to maintain membership independently. Keywords: Brand Recognition; Brand Attitude; Continuance Intention; Social Security; BPJS Ketenagakerjaan; Public Services